Sculpting the brain - Garcia-Lopez, Pablo (Frontiers in Human Neuroscience, 2012)
Neuroculture, conceived as the reciprocal interaction between neuroscience and different areas of human knowledge is influencing our lives under the prism of the latest neuroscientific discoveries. Simultaneously, neuroculture can create new models of thinking that can significantly impact neuroscientists' daily practice. Especially interesting is the interaction that takes place between neuroscience and the arts. This interaction takes place at different, infinite levels and contexts. I contextualize my work inside this neurocultural framework. Through my artwork, I try to give a more natural vision of the human brain, which could help to develop a more humanistic culture.